Evaluation of Triazole and Strobilurin Fungicides against Leaf and Panicle Blast of Rice in Farmer’s Field - Adhikari, Nirmal; Katel, Shambhu (Journal of the Plant Protection Society, 2023)
Blast disease of rice caused by the ascomycetes fungus Magnaporthe grisea poses a major threat to rice production from terai to hilly region of Nepal. Field trials were conducted in two successive years, 2021 and 2022 at Bharatpur-5, Chitwan in a farmer's field producing seed of Hardinath-1 variety with the main objective of finding the effective single and/or pre-mix formulation of triazole and strobilurin fungicides against rice blast that could be an alternative to tricyclazole. The trials were conducted in randomized complete block design with three replications and eight treatments viz. azoxystrobin 18.2% + difenoconazole 11.4% SC, propiconazole 13.9% + difenoconazole 13.9% EC, azoxystrobin 11% + tebuconazole 18.3% SC, azoxystrobin 23% SC, propiconazole 25% EC, difenoconazole 25% EC, tebuconazole 25%WDG and a control. The fungicides were applied during tillering and heading stage at the rate of 0.1%. All fungicides significantly reduced the leaf and panicle blast severity resulting in a higher yield. Among the tested fungicides, pre-mix formulation fungicide azoxystrobin 18.2% + difenoconazole 11.4% SC, propiconazole 13.9% + difenoconazole 13.9% EC and azoxystrobin 11% + tebuconazole 18.3% SC gave excellent performance with the lowest leaf and panicle blast severity and higher yield. Hence, these three fungicides could be used for the management of leaf and panicle blast disease for higher yield. However, controlling rice blast disease has become increasingly challenging due to the pathogens' capacity to adapt and evolve into new, more potent strains, making the management and control of this disease more difficult.